UPAYA GURU DALAM MENGATASI DAMPAK LEARNING LOSS PADA KEMAMPUAN MENULIS SISWA KELAS IV DI SDN 1 PATUKANGAN - Nadilla Ananda (STKIP Subang, 2025)
This study aims to analyze teachers' efforts to address the impact of learning loss on fourth-grade students' narrative writing skills at SDN 1 Patukangan. Based on the problem of low narrative writing skills, this descriptive qualitative study focuses on the causes of learning loss, the obstacles experienced by teachers, and the implementation of teacher strategies. Data were collected through observation, interviews, documentation, and assessment of narrative writing products. The results showed that teachers implemented strategies such as directing students to read, utilizing visual media, and implementing practice and field trip methods. However, teachers faced several obstacles, including students' lack of ability to compose essays, low reading interest, and lack of interest in learning. These efforts included diagnostic assessments, repetition of essential material, use of interactive media, gradual guidance, and providing personalized feedback.